Bofill: the French Adventure and the Launch of an International Career - Serrell, Dominique (Histories of Postwar Architecture, 2024)
This text is a special contribution to this monographic issue on Ricard Bofill Taller de Arquitectura, commissioned from Dominique Serrell, author of Bofill. Les années françaises / The French Years, published by Norma Éditions in 2023. As the former director of the Taller de Arquitectura in Paris, Serrell provides a comprehensive analysis of Bofill’s principal projects and achievements during his career in France between 1971 and 1985.